Assertiveness and self-esteem among nurses working at tertiary hospital, Jumla, Nepal - Maharjan, Ramu; Lama, Monika; Pahadi, Nirmala Kumari; Mahat, Dhan Laxmi (Journal of Karnali Academy of Health Sciences, 2026)
Introduction: In healthcare system, nurses play a critical role in patient care, often working in high-stress environments that demand effective communication and rapid decision-making. Assertiveness and self-esteem are essential personal attributes that influence nurses’ professional performance, and quality of care. Despite their importance, these attributes are often overlooked in nursing professional development hence, the study aimed to assess the level of assertiveness and self-esteem among nurses.Methods: A descriptive cross-sectional study was conducted among 101 registered nurses working at Karnali Academy of Health Sciences (KAHS), Jumla, using a total enumerative sampling technique. From 4th January to 15th January 2026 the data were collected through a self-administered structured questionnaire comprising socio-demographic and professional information, the Simple Rathus Assertiveness Schedule (SRAS), and the Rosenberg Self-Esteem Scale (RSES). Data were analyzed using SPSS version 16 with descriptive statistics and inferential tests (Chi-square and Fisher’s exact test).Results: More than half of the respondents had high levels of assertiveness (50.5%) and self-esteem (51.5%). No statistically significant association was found between assertiveness and socio-demographic or professional characteristics. However, self-esteem showed a statistically significant association with religion (p = 0.027) and professional designation (p = 0.049).Conclusion: The study revealed that nearly half of the nurses exhibited low levels of assertiveness and self-esteem, highlighting a potential area of concern for nursing practice and well-being. The findings underscore the need for targeted interventions, such as assertiveness training and self-esteem enhancement programs, to strengthen nurses’ communication skills, confidence, and professional effectiveness.